Pembuatan Surfaktan Berbahan Dasar Jerami Padi - Sri Wahyu Murni (Eksergi)
Indonesia's oil production has declined due to the low level of production of oil wells that have been old. Extraction of oil from the wells can be enhanced by the injection of surfactant. Potential raw material for the manufacture of surfactants, especially the waste material so that lower-priced. This material include lignocellulosic materials and plantation agricultural waste. Rice straw is one of them. This study aims to make surfactants from rice straw. The axpetriment was conducted through the steps of: (1) preparation of raw materials, (2) delignification and isolation of lignin, (3) sulfonation of lignin using NaHSO3 . Delignification of rice straw held at a temperature of 166o C and a pressure of 1.2 atm. Sulfonated of lignin conducted at a temperature of 90-95°C and pH 7. Lignin and sodium lignosulfonate tested using FTIR and gravimetric. The results show at 2.5 g lignin, weight percent of NaHSO3  60% of the weight of lignin, pH 7, temperature 90-95 ° C for 4 hour reaction obtained 2,5509 g of sodium lignosulfonate (SLS). Sodium lignosulfonate is soluble in water. Sodium lignosulfonate phase behavior test using crude oil from Oil Drilling Tanjung, South Kalimantan, at the surfactant concentration 3000 and 5000 ppm result that the type of emulsion is water in oil. So that this surfactant not suggested for EOR.